2023
DOI: 10.5796/electrochemistry.23-67010
|View full text |Cite
|
Sign up to set email alerts
|

β-Scission by Direct Electrochemical Oxidation: Proton-coupled Electron Transfer Mechanism Dictated by Synthetic Study and Computations

Abstract: β-Scission from alkoxy radical enables selective Csp3-Csp3 bond cleavage under ambient conditions, offering a useful method for organic synthesis. Various photocatalytic systems for β-scission have been reported, where proton-coupled electron transfer (PCET) mechanism plays a key role in the generation of alkoxy radical and thus β-scission. Electrochemical β-scission has been mainly pioneered in the presence of mediator, and a direct electrochemical system has rarely been investigated. Here, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A decrease in the oxidation current can be considered as a decrease in the diffusion coefficient of the hydrogen bond complex; thus, we attempted to reproduce the CV pattern by computational simulation (Figures S1 and S2 in Supporting Information File 1 ) [ 16 ]. The results indicated that an excessively small diffusion coefficient (1/10- or 1/100-fold) is required to reproduce a CV pattern similar to that observed experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…A decrease in the oxidation current can be considered as a decrease in the diffusion coefficient of the hydrogen bond complex; thus, we attempted to reproduce the CV pattern by computational simulation (Figures S1 and S2 in Supporting Information File 1 ) [ 16 ]. The results indicated that an excessively small diffusion coefficient (1/10- or 1/100-fold) is required to reproduce a CV pattern similar to that observed experimentally.…”
Section: Resultsmentioning
confidence: 99%